Integrated land-use models for spatial planning support: country-specific solutions - Vilja Vaszóczik; Erzsébet Vajdovich-Visy (DETUROPE)
The key issue of contemporary planning is that it has to work within and respond to the scarcity of resources. The competition for land is particularly intense in growth areas, especially around cities, where suburbanisation is accelerating and causes fundamental change of the evolved settlement pattern and the structure of land use. Planning in this situation must perform the difficult role of mediator in the competition for land, guiding the growth process and at the same time saving and protecting the open spaces which are indispensable for healthy living and are significant natural heritage. The integrated decision support systems (DSS) are more and more popular among spatial planners and decision makers since 2000. These systems facilitate to incorporate scientific knowledge in the decision making process. During the last years in the unit for spatial planning of the Lechner Knowledge Centre we developed for a country specific spatial decision support, the Hungary Spatial Decision Support model. This study introduces this model and how it can assist territorial planning and decision making.